A review on enhancements of PMMA Denture Base Material with Different Nano-Fillers. Issue 1 (1st January 2021) - Ali Sabri, Ban; Satgunam, Meenaloshini; Abreeza, NM; N. Abed, Abdulrahman
Abstract: Poly methyl methacrylate (PMMA) is the dominant acrylic that is widely used to produce partial and complete dentures. Denture fractures are caused by fatigue owing to repetitive masticatory, flexural and impact loads produced by dropping. The mechanical properties of dentures have been developed by reinforcing with various agents like rubbers, fillers and fibers. Progressively, novel dental materials reinforcement tactics have been developed following the advancement in Nano dentistry. Nonetheless, the issue pertaining to the superior mechanical properties of the PMMA still exists albeit it's biocompatible and aesthetic properties. In recent years, the nanostructure materials have received much attention due to their high surface area to volume ratio that boosts interaction and delivers new biological, physical, and chemical characteristics. Many studies have evaluated the usage of nanotubes and nanofiber in dental composites, however, the data estimating the reinforcement issue of nanotubes and nanofibers in PMMA have been scarce. This article is aimed to review the progress related to the development of mechanical properties of denture base materials in addition to the latest advances and prospective developments for PMMA acrylic resins reinforcement. Poly methyl methacrylate PMMA composites, strengthening of dentures, Nano-fillers surface treatment, biomedical Nano additives for mechanical improvement, Nano-fillers of PMMA, biomedical ceramic Nano-fillers, biomedical metallic materials as Nano-fillers, hybrid reinforcement of PMMA, biocompatibility of polymeric PMMA composite, biomaterial for dental applications.